2022
DOI: 10.1186/s13071-022-05593-0
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin decreases fecundity in the Asian malaria vector Anopheles stephensi by inhibiting the target of rapamycin signaling pathway

Abstract: Background Mosquito-borne diseases threaten human health, but mosquito control faces various challenges, such as resistance to chemical insecticides. Thus, there is an urgent need for more effective and environment-friendly control agents. Capsaicin can downregulate the mTOR signaling pathway of tumor cells. The TOR signaling pathway can mediate the expression of vitellogenin (Vg) to regulate the fecundity of insects. Whether capsaicin has the potential to inhibit fecundity of mosquitoes by reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…While Anopheles stephensi mosquitoes accepted a 10% sugar solution with 50 µmol L −1 capsaicin for two days, after blood feeding on mice the treated females showed a reduction in the number of eggs laid. The reduction in fertility was caused by capsaicin inhibition of the TOR signaling pathway 67 . Ae.…”
Section: Discussionmentioning
confidence: 99%
“…While Anopheles stephensi mosquitoes accepted a 10% sugar solution with 50 µmol L −1 capsaicin for two days, after blood feeding on mice the treated females showed a reduction in the number of eggs laid. The reduction in fertility was caused by capsaicin inhibition of the TOR signaling pathway 67 . Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, BCAAs are widely believed to activate the mTOR cell signaling pathway, thereby initiating protein synthesis in skeletal muscle and the intestine [51,52]. The mTOR pathway regulates growth, molting, and cell differentiation in crustaceans [53,54], and more importantly, it regulates the expression of vitellogenin to control oocyte maturation, ovarian development, and fecundity in invertebrates [8]. Therefore, exogenous BCAAs are necessary during the maturation process of this species.…”
Section: Total Protein and Amino Acid Contentsmentioning
confidence: 99%
“…It is well-known that the gonadal development process of crustacea is influenced by critical nutrients. The nutrition intake of broodstocks determines the nutritive value of the ovary, hepatopancreas, and muscle of P. trituberculatus, which affects commercial quality [7] and the ovarian maturation process [8,9]. Some key nutrients, such as amino acids and fatty acids, have been proven to play important roles in regulating the reproductive performance of animals [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike conventional ryanodine receptor insecticides, Tyclopyrazoflor exhibits a distinctive structure characterized by a unique amide group (Figure 19). Capsaicin ( 36) is a natural alkaloid obtained from the mature fruit of the capsicum [113]. Studies have shown that capsaicin has a stimulating effect in various species, can function as a repellent, and can also influence the egg-laying decisions of various insects [113][114][115].…”
Section: Insecticides/acaricides Containing a Long Chainmentioning
confidence: 99%